Direct patient reporting of adverse drug reactions: An analysis of spontaneous reports submitted to Malaysian pharmacovigilance centre - Hariraj, Vidhya; Aziz, Zoriah (Pharmacotherapy Group, University of Benin, Benin City, 2018)
Purpose: To evaluate patient adverse drug reaction (ADR) reports in terms of categories by System Organ Class (SOC), suspected products and seriousness. Methods: The national database was retrospectively searched from 2008 to 2015. ADR reports by patients were included but vaccine-related reports and reports by healthcare professionals were excluded. Eligible reports were analysed descriptively and Chi-square test was used to evaluate the association of various categorical variables with serious ADRs. Results: Of the total of 75,391 reports screened in the National ADR database for the study period, only 81 (0.11 %) were reports from patients, of which 32 (40 %) reports involved serious ADRs. The majority of reports was associated with unregistered products or unapproved cosmetics. Half of the reports involved traditional products while cosmetic products constituted another 10 % of the reports. The three main SOCs involved were skin and appendages disorders (26 %), body as a whole (25 %), and central and peripheral nervous system disorders (9 %). A total of 23 out of 47 products tested were adulterated with prescription drugs while 4 cosmetic products exceeded the permitted limit for hydroquinone or mercury. Two factors found to be significantly associated with serious ADRs were product registration status and presence of adulteration. Conclusion: The findings indicate that patient reporting of suspected ADRs has the potential to add valuable information to pharmacovigilance.